2023
DOI: 10.1021/acs.jpca.3c00048
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Metastable Argon Optical Excitation and Gain in Ar/He Microplasmas

Abstract: The optically pumped rare-gas metastable laser is capable of high-intensity lasing on a broad range of near-infrared transitions for excited-state rare gas atoms (Ar*, Kr*, Ne*, Xe*) diluted in flowing He. The lasing action is generated by photoexcitation of the metastable atom to an upper state, followed by collisional energy transfer with He to a neighboring state and lasing back to the metastable state. The metastables are generated in a high-efficiency electric discharge at pressures of ∼0.4 to 1 atm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…Wang et al [8,9] recently proposed a new scheme for extracting lasing in a plasma jet, potentially overcoming the power-scaling obstacles in previously used confined discharges. Until now, most research on DPRGLs has been carried out using Ar* as the gain medium [15][16][17][18] and a little on the Xe* laser [5,19,20] . The only research for the Kr* laser is on concept verification and kinetics investigation [1,21] , and no study using high-power diode pumping has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [8,9] recently proposed a new scheme for extracting lasing in a plasma jet, potentially overcoming the power-scaling obstacles in previously used confined discharges. Until now, most research on DPRGLs has been carried out using Ar* as the gain medium [15][16][17][18] and a little on the Xe* laser [5,19,20] . The only research for the Kr* laser is on concept verification and kinetics investigation [1,21] , and no study using high-power diode pumping has been reported.…”
Section: Introductionmentioning
confidence: 99%